Contact lens procurement and usage habits among adults in Sudan. - Yazan Gammoh (Public Library of Science (PLoS), 2021)
Objective The study aimed to assess contact lens (CL) wear and care habits among adults in Sudan. Design An observational, non-interventional, multi-center, cross-sectional study was conducted in the CL departments of all the eye hospitals and centers, and optical centers in the Khartoum State, Sudan. Participants Established CL wearers residing in Khartoum State, Sudan. Main outcomes and measures CL wear profile, CL usage habits, hand and CL hygiene habits were assessed using an interviewer-administered questionnaire. Results The average age of the 442 participants was 24.57 (± 4.87) years. Women comprised 92% of the sample. Smoking was reported by 15.8% of the sample. 81.9% wore soft spherical CL, with 43.4% of the participants were prescribed CL on a yearly replacement schedule. Only 68.3% were prescribed CL by an eye care practitioner. Multipurpose solutions were used by 78.8% of the sample to clean CL, and by 52% to clean the lens case. Compliance rate for CL wear and care among participants was 81.1%. None of the participants reported sharing CL or CL case and rinsing the case with tap water. High compliance level was observed for overnight wear; swimming and showering with CL; handwashing before CL insertion; and cleaning of CL. Moderate compliance rates were recorded for cleaning and replacing lens case, and topping up or sharing solution. Low compliance was noted for attending after care visits. Conclusions and relevance CL wearers in Sudan exhibit high to moderate levels of compliance to most contact lens wear and care aspects, except for attending aftercare visits. CL practitioners in Sudan are encouraged to prescribe CL appropriate to the lifestyle and economic situation of patients and actively recommend care products. In addition, practitioners need to follow up with patients to attend aftercare appointments, where hygienic wear and care habits should be emphasized.